Formulating palm-based nanoemulsion in room temperature ionic liquids - Tuan Kob Yaakub, Tuan Nurul Azura; Abdul Rahman, Mohd Basyaruddin; Mohammad Latif, Muhammad Alif (Medwell Publications, 2019)
The ability of Room Temperature Ionic Liquids (RTILs) to support the self-aggregation of amphiphilic molecules such as non-ionic surfactants have enhanced their applications in the industry. The aim of the present study is to formulate and investigate the properties of surfactant/RTILs and surfactant/RTILs/oil aggregation intended for separation processes. The aggregation behaviour of a non-ionic surfactant, Tween80 in 1-butyl-3-methylimidazolium hexafluorophosphate (bmimPF6) and 1-butyl-3-methylimidazolium tetrafluoroborate (bmimBF4) was determined by measuring the surface tension of surfactant/RTILs mixture at different concentration ratios. The resulting Critical Micelle Concentrations (CMCs) were compared with the ones in the water. The CMCs of Tween80 in bmimPF6 and in bmimBF4 were found to be much higher than that in water under the same condition. The relatively low solvophobicity between RTILs and the hydrophobic tail of Tween80 led to increased CMCs. The aggregation behaviour of Tween80 in RTILs was further investigated in the presence of an oil phase. The added Palm Oil Ester (POEs) induced the formation of oil-in-RTIL nanoemulsions. These nanoemulsions were prepared using low energy method and were characterized using Zetasizer measurement and transmission electron microscopy. The particle size of Tween80/bmimBF4 / POE were found comparable to the ones in water. The results showed that the introduction of oil phase produced a diverse effect towards hydrophobic and hydrophilic RTILs.